A case study regarding Ecuadorian farmers’ perspective on associative work in agriculture - Renzo Antonio Ceme Vinces; Amy Boren-Alpizar; Jason Headrick; David L Doerfert; Pablo Lamiño Jaramillo (Journal of International Agricultural and Extension Education, 2024)
This qualitative case study conducted in Ecuador aimed to explore the perspective of a group of farmers regarding agricultural associative work and assess their association's strengths, weaknesses, opportunities, and threats (SWOT analysis). The research is theoretically framed through the social capital theory and utilizes various methods, including one-on-one interviews, team group activities, flipcharts, field notes, and research memos. Four main topics emerged from the analysis: the importance of associative work, common goals and values, advantages and barriers of being part of the association. Participants expressed diverse perspectives on associative work, primarily focusing on the benefits and advantages of being associated. They perceived membership in an agricultural association positively and identified clear advantages of being part of it. The SWOT analysis revealed that product quality was the main strength of the association. However, the principal weakness was the lack of infrastructure, hindering the association's operations and growth. The most significant opportunity identified was the need for technical assistance to enhance agricultural practices and productivity. The most repetitive threat was the challenge of low productivity due to climate change, which poses a significant risk to the farm sector. Recommendations were made to consider the perspectives of other farmers' associations to gain additional insights into the role of such associations in Ecuadorian agriculture. Organizations working with small farmers are suggested to evaluate the current state of the associations they collaborate with. Conducting SWOT analyses will enable a comprehensive needs assessment of agricultural organizations, allowing for targeted interventions and support.
Keywords: farmers’ association; agriculture; associative work; SWOT analysis; case study